Pelaksanaan Tanggung Jawab Perusahaan Outsourcing (PT. Mitra CahayaNusantara Pelalawan) Terhadap Pekerja/Buruh - Addina '; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Outsourcing defined as the utilization of labor to produce or implement a job by a company through a provider of labor. In the implementation of the system outsourcing rules must be made based on the rules that have been set that is in accordance with Law No. 13 of 2003 about manpower . Climate business competition is getting tighter, the company tries to make production cost efficiency (cost of production). One of the solution is with the system of contract employees, where with this system the company can save expenses in finance human resources working in the company concerned. In this case still the occurrence of violations committed by outsourcing companies where in practice still not in accordance with the rules that have been determined. One of them is done by PT. Mitra Cahaya Nusantara Pelalawan, this action certainly requires a responsibility that must be implemented by the company in order to provide welfare to workers / laborers who work. The problem that will be discussed in this thesis is how the responsibility of outsourcing company (PT Mitra Cahaya Nusantara) toward the labor .This type of the research is sociological, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear about the problem of the research . This research was conducted at PT. Mitra Cahaya Nusantara Pelalawan, while the population and sample are all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collection techniques in this study with interviews, questionnaires and literature study .The result of the research, it can be concluded that Corporate Responsibility Outsourcing (PT Mitra Cahaya Pelalawan) has not run well and maximum. The existence of constraints faced that cause the company difficult to run outsourcing system properly. To overcome this problem, it is advisable to tighten the supervision of companies engaged in outsourcing and for workers / laborers more trying to understand the rights and obligations that they should accept it based on the rules of the laws that have governed it.Keyword : Responsible – Outourcing - workers / laborers